Feed Values of Sunflower Heads and Stovers Treated with Different Methods and Possibilities of Using as Roughage - B.zehra Sarıçiçek; Ali Vaiz Garipoğlu (Journal of Agricultural Sciences)
This study was carried out to determine the effects of different urea treatments 4% urea; US. 4% urea+molasses; UMS, and 4% urea+soybean extract treated stovers and heads; USS on the digestibilities of the -sunflower stovers and heads and also to determine the possibilities of utilizing of these stovers and heads as an alternative roughage source. Four native Karayaka hoggets were used in digestion trial. Digestibility coefficients related to dry matter, organic matters, crude protein of the untreated stovers and heads UTS , US, UMS, and USS were determined as; 35.771, 46.232, 6.037 %; 42.478, 47.742, 37.916%; 62.334, 51.085, 45.311%; 55.232, 59.340, 56.330%, respectively. Energy values SV were determined as; 5.468, 14.353, 15.550, 26.757 SV, respectively. Fattening period was 70 days and animal materials were 40 hoggets.Total weight gains, daily weight gains, daily forage intakes, daily concentrate intakes and feed efficiency ratios feed/gain were found as: 7.02, 7.54. 7.70, 9.23 Kg; 100.00±12.95, 107.72±15.78, 109.57±11.56, 127.43±15.70 g; 553.86, 550.00, 574.36, 575.86 g; 599.21, 592.43, 598.21, 598.79 g; 11.53, 10.61, 10.71, 9.22 for UTS, US, UMS, and USS, respectively.